Novel SMAD3 p.Arg386Thr genetic variant co‐segregating with thoracic aortic aneurysm and dissection. Issue 4 (5th February 2020) - Engström, Karolina; Vánky, Farkas; Rehnberg, Malin; Trinks, Cecilia; Jonasson, Jon; Green, Anna; Gunnarsson, Cecilia
Abstract: Background: Pathogenic variants in the SMAD3 gene affecting the TGF‐β/SMAD3 signaling pathway with aortic vessel involvement cause Loeys‐Dietz syndrome 3, also known as aneurysms–osteoarthritis syndrome. Methods: Description of clinical history of a family in Sweden using clinical data, DNA sequencing, bioinformatics, and pedigree analysis. Results: We report a novel SMAD3 variant, initially classified as a genetic variant of uncertain clinical significance (VUS), and later found to be co‐segregating with aortic dissection in the family. The index patient presented with a dissecting aneurysm of the aorta including the ascending, descending, and abdominal parts. Genotype analysis revealed a heterozygous missense SMAD3 variant: NM_005902.3( SMAD3 ): c.11576G > C (p.Arg386Thr). The same variant was also identified in a 30 years old formalin‐fixed paraffin‐embedded block of tissue from a second cousin, who died at 26 years of age from a dissecting aneurysm of the aorta. Conclusion: A "variant of uncertain significance" according to the ACMG guidelines has always a scope for reappraisal. Genetic counselling to relatives, and the offering of surveillance service is important to families with aortic aneurysm disease. The report also highlight the potential use of FFPE analysis from deceased relatives to help in the interpretation of variants. Abstract : Pathogenic variants in the SMAD3 gene affecting the TGF‐β/SMAD3 signaling pathway with aortic vessel involvement cause Loeys‐Dietz syndrome 3, also known as aneurysms‐ osteoarthritis syndrome. Here, we report a novel SMAD3 variant, initially classified as a genetic variant of uncertain clinical significance (VUS), and later found to be co‐segregating with aortic dissection in the family. The index patient presented with a dissecting aneurysm of the aorta including the ascending, descending and abdominal parts.Genotype analysis revealed a heterozygous missense SMAD3 variant: NM_005902.3(SMAD3): c.11576G>C (p.Arg386Thr).